Aportaciones y Límites de los Paradigmas Cognitivo y Dialógico en Educación Moral - Martín, Xus (Teoría de la Educación. Revista Interuniversitaria, 2009)
The following article tries to clarify and define the basic essentials of a particular understanding of moral education. To be exact that developed by the cognitive and dialogical paradigms in psycoiogy ana etmcs respectively. Therefore the contributions of Habermas and Kohlberg will be briefly described, and some of the criticism recieved will be presented, the consideration of which can complement the original contribuionts of both authors. The aim of this process is to note down the foundations of a moral education based on the respect for personal autonomy and on the capacity to generate values of justice and solidarity.